Good and Bad News from China's New Cooperative Medical Scheme - Linxiu Zhang; Hongmei Yi; Scott Rozelle (IDS Bulletin, 2010)
Abstract The overall goal of this article is to understand the progress in implementing the New Cooperative Medical Scheme, while seeking to assess the strengths and weaknesses of the programme and, in particular, to understand its effects on the incidence of catastrophic medical payment. The study is based on two rounds of nationally representative household survey data collected in 2005 and 2008. The study found that the programme has a very high level of participation, and has increased farmers' use of medical services. However, despite efforts by both central and local governments and high household participation, the programme is only partially achieving its policy objectives. In particular, it has been able to extend to almost all of the rural population, but has failed to cover expenses for catastrophic illness, due to insufficient funds.